Analysis Of Efficiency Of Windu Shrimp Cultivation Business Policulture System In Tugurejo Sub-District Tugu Districts Semarang City - Sulistyowati Sulistyowati (Jurusan Perikanan dan Kelautan, 2020)
This study aims to calculate technical efficiency and determine the financial efficiency of the cultivation of windu shrimp with the Polyculture system by farmers in Tugurejo village, Tugu district, Semarang City based on simple investment criteria, namely BC ratio (Benefit Cost Ratio), BEP (Break Event Point), ROI (Revenue On Invensment) to measure how much efficiency the use of capital is against revenue. The method used is descriptive analysis with a questionnaire and field observations. The data used are primary data collected through interviews with respondents and key persons. The sample was 25 people so that all (census) were taken in October 2019-March 2020. The results showed that the BC ratio analysis was 1.64, BEP (Q) tiger prawns were 160.49 kg / Ha per year and for BEP prices IDR 35,680 / kg, BEP (Q) of milkfish as much as 755.25 kg / Ha per year and for BEP prices of IDR 12,175 /kg, ROI is 137.97%> 100%, the tiger prawn cultivation business with an efficient polyculture system in the use of capital to revenue and worthy of cultivation.